Diskursus Pangan, Ekofeminisme dan Food Sovereignty di Era COVID-19 - Wahyu Eka Styawan (Pusat Studi Gender Universitas Jember, 2022)
During the COVID-19 pandemic, many sectors experienced shocks, not the food sector. In the food sector, there are still many problems facing difficulties from the presence of the COVID-19 wave. Some of the contributing factors are the transformation of agriculture from traditional to modern. Since the introduction of the green revolution, food has led to an intensification framework ranging from global agricultural food production and a focus on productivity, such as requiring farmers to grow monocultures. This condition causes land degradation, environmental degradation and biodiversity so that in the long term food security is threatened. Quantity-based intensification also causes local wisdom of farmers' agriculture, such as farmers' attachment to the ecosystem, the ability to produce local seeds, and the determination of subsistence factors, one of which is the barn system. On the other hand, besides having an impact on the ecological aspect, it also has an impact on gender, which in the end leads to women's injustice. Several notes in previous research have found that agricultural intensification resulted in a gender burden in farmer households, as well as an increased burden on female farmers. The disconnection of farmers from the ecosystem, the threat of ecological cracks and gender climate change, are links that cannot be separated, because they affect each other. This paper will describe and analyze the problem of food insecurity; pay attention to gender and ecological gaps using ecofeminism and food sovereignty approaches as an effort to reconstruct the existence of food insecurity; and learn from the experience of the COVID-19 pandemic.